POST-TRAUMATIC GROWTH AMONG TSUNAMI SURVIVORS: THE IMPACT OF PROBLEM-FOCUSED COPING ON LONG-TERM RECOVERY - Hidayati, Siti Hajar Sri; Utami, Muhana Sofiati (JURNAL AL-IJTIMAIYYAH, 2025)
The 2004 Indian Ocean tsunami caused catastrophic damage in Aceh-Indonesia, leaving profound psychological impacts on survivors. This study examines the long-term role of problem-focused coping in predicting post-traumatic growth (PTG) among 145 adult survivors who lost close family members. Using the Post-Traumatic Growth Scale and the Problem-Focused Coping Scale, the results show that problem-focused coping significantly predicts PTG, accounting for 52.34% of the variance (p < 0.001). Survivors who employed active, constructive coping strategies displayed greater growth, meaning-making, and personal development nearly two decades after the trauma. These findings underscore the enduring significance of adaptive coping and the importance of incorporating culturally grounded values into post-disaster mental health interventions.